2014
DOI: 10.1002/chem.201403028
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐Directed Dimeric versus Tetrameric Assemblies of Lanthanide‐Stabilized Dilacunary Keggin Tungstogermanates

Abstract: Reaction of mid- to late lanthanide ions with GeO2 and Na2WO4 in NaOAc buffer results in a library of [Ln2 (GeW10O38)](6-) clusters (Ln2), which consist of dilacunary Keggin fragments stabilized by the insertion of 4f atoms in the vacant sites and show the ability to undergo cation-directed self-assembly processes. In the presence of Na(+), two β-Ln2 subunits assemble by means of Ln-O(WO5)-Ln bridges to form the chiral [Ln4(H2O)6(β-GeW10O38)2](12-) dimeric anions (ββ-Ln4, Ln = Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…showed that {GeW 10 } fragments can also be formed in situ by direct reaction of Na 2 WO 4 , GeO 2 , and lanthanide sources in acetate buffer 6d. g, 10j…”
Section: Resultsmentioning
confidence: 99%
“…showed that {GeW 10 } fragments can also be formed in situ by direct reaction of Na 2 WO 4 , GeO 2 , and lanthanide sources in acetate buffer 6d. g, 10j…”
Section: Resultsmentioning
confidence: 99%
“…Analogous studies carried out for mid-to-late lanthanides showed that dimerica nions based on similar Ln 2 subunits were obtained for Ln = Gd to Lu in the presence of exclusively Na + ,w hereas tetrameric speciesw ere isolated for Ln = Ho to Lu when Cs + wasa dded. [15] NeitherK + nor [Ni(H 2 O) 6 ] 2 + played any structuralroleinthis case. The variety of POM frameworks afforded by this approach led us to extend our work to the whole group of early lanthanides (Ln = La to Sm) to explore whether additional Ln 2 -based POM aggregates exist.…”
Section: Synthetic Aspectsmentioning
confidence: 94%
“…[14] The use of mid-to-late lanthanides insteado fC e III led to the isolation of smaller dimeric or tetrameric species. [15] These POMa ggregates are all based on different but closely related[ Ln 2 GeW 10 O 38 ] 6À (Ln 2 ) subunits and they show complex behavior in aqueous solution that originates from partial fragmentation upon dissolution with consequent dissociation into oligomers and/ori ndividual Ln 2 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Although Pr1 exhibits distortedm onocapped square-antiprismatic geometry and Pr2 adopts at ricapped triangular prism geometry,t hey are both nine-coordinated andt heir coordination environment is very similar (Figure 2b) (19) ), and one m 3oxo atom (O89/O93;P r1ÀO: 2.604 (14) ;P r2ÀO: 2.592 (15) ), which is coordinated to one Se atom and one Wa tom from the {Se 2 W 7 O 30 H 2 }u nit and one Pr1/Pr2 atom simultaneously (Figure 2a). In contrast, Pr3 is eight-coordinated in ab icapped triangularp rism geometry,w hich is coordinated to twoa vailable terminal oxygen atoms from the {Se 2 (2) ), and one m 3 -oxo atom (O84;P r3ÀO: 2.561 (15) ), which is coordinatedt oo ne Se atom and one Wa tomf rom the {Se 2 W 7 O 30 H 2 }u nit and one Pr3 atom (Figure 2b).…”
Section: Structural Descriptionmentioning
confidence: 99%
“…The diversity of polyoxometalates (POMs) has never ceasedt o amaze us with their aesthetically pleasing structures and their potentiala pplicationsi nm any areas, such as catalysis, medicine, magnetism, andm aterials science. [1][2][3][4][5][6] In the context of designing and synthesizing polynuclear clusters, of particular interestt os cientific researchers is the fact that polynuclear anionic metal-oxo clusters can be formed throught he assembly of small oxometalate units (traditionally W, Mo, or V) by controlling flexible reaction parameters (e.g.,p H, temperature, molar ratio of the reactants, reactions olvents). [7][8][9] Perhaps based on this concept, an especially enlightening versatile one-pot self-assembly synthesis remains an important synthetic strategy to construct high-nuclearity polyoxotungstates (POTs), particularly POTst hat contain nonconventional heteroatoms Se IV and Te IV ,w hichm ainly result from the difficulty of separating as table synthetic Se IV or Te IV precursor.…”
Section: Introductionmentioning
confidence: 99%